Planning Spacecraft Activities: An Automated Approach - Policella, Nicola; Oliveira, Henrique; Benzi, Edoardo (Proceedings of the International Conference on Automated Planning and Scheduling, 2013)
In 2013 the Alphasat spacecraft will be launched: in addition to its main commercial payload, four Technology Demonstration Payloads (TDPs) will fly on-board. The different payloads are provided by different research institutes, which will be able to define in-orbit demonstration tests of these new technologies. To optimize this opportunity, coordination of the different, possibly conflicting, payload operations is required. A software system to support the management of the TDP operations has been developed. While this system is intended to be completely automated (i.e., without any human intervention in the nominal case), it has been designed to keep all the different users (system and TDP operators) in the loop. This paper presents this system and in particular focuses on its core: the planning engine.